Heterologous expression of cyclodextrin glycosyltransferase from Paenibacillus macerans in Escherichia coli and its application in 2-O-α-D-glucopyranosyl-L-ascorbic acid production - Yujia Jiang (BMC Biotechnology, 2018)
Abstract Background Cyclodextrin glucanotransferase (CGTase) can transform L-ascorbic acid (L-AA, vitamin C) to 2-O-α-D-glucopyranosyl-L-ascorbic acid (AA-2G), which shows diverse applications in food, cosmetic and pharmaceutical industries. Results In this study, the cgt gene encoding α-CGTase from Paenibacillus macerans was codon-optimized (opt-cgt) and cloned into pET-28a (+) for intracellular expression in E. coli BL21 (DE3). The Opt-CGT was purified by Ni2+-NTA resin with a 55% recovery, and specific activity was increased significantly from 1.17 to 190.75 U·mg− 1. In addition, the enzyme was adopted to transform L-AA into 9.1 g/L of AA-2G. Finally, more economic substrates, including β-cyclodextrin, soluble starch, corn starch and cassava starch could also be used as glycosyl donors, and 4.9, 3.5, 1.3 and 1.5 g/L of AA-2G were obtained, respectively. Conclusions N-terminal amino acid is critical to the activity of CGTase suggested by its truncation study. Furthermore, when the Opt-CGT was flanked by His6-tags on the C- and N-terminal, the recovery of purification by Ni2+-NTA resin is appreciably enhanced. α-cyclodextrin was the ideal glycosyl donor for AA-2G production. In addition, the selection of low cost glycosyl donors would make the process of AA-2G production more economically competitive.